Inhibition of RecA-mediated cleavage in covalent dimers of UmuD. - Lee, M H (1996)
Disulfide-cross-linked UmuD2 derivatives were cleaved poorly upon incubation with activated RecA. Reducing the disulfide bonds prior to incubating the derivatives with RecA dramatically increased their extent of cleavage. These observations suggest that the UmuD monomer is a better substrate for the RecA-mediated cleavage reaction than the dimer.